N1303K (c.3909C>G) Mutation and Splicing: Implication of Its c.[744-33GATT(6); 869+11C>T] Complex Allele in CFTR Exon 7 Aberrant Splicing. (17th May 2015) - Farhat, Raëd; Puissesseau, Géraldine; El-Seedy, Ayman; Pasquet, Marie-Claude; Adolphe, Catherine; Corbani, Sandra; Megarbané, André; Kitzis, Alain; Ladeveze, Véronique
Abstract : Cystic Fibrosis is the most common recessive autosomal rare disease found in Caucasians. It is caused by mutations on the Cystic Fibrosis Transmembrane Conductance Regulator gene ( CFTR ) that encodes a protein located on the apical membrane of epithelial cells. c.3909C>G (p.Asn1303Lys, old nomenclature: N1303K) is one of the most common worldwide mutations. This mutation has been found at high frequencies in the Mediterranean countries with the highest frequency in the Lebanese population. Therefore, on the genetic level, we conducted a complete CFTR gene screening on c.3909C>G Lebanese patients. The complex allele c.[744-33GATT(6); 869+11C>T] was always associated with the c.3909C>G mutation in cis in the Lebanese population. In cellulo splicing studies, realized by hybrid minigene constructs, revealed no impact of the c.3909C>G mutation on the splicing process, whereas the associated complex allele induces minor exon skipping.